Evaluation of positive ductal margins of biliary tract cancer in intraoperative histological examination - Ueda, Junji (Oncol Lett, 2018)
At present the only method available to confirm microscopic infiltration of cancer into ductal margins during surgery, is intraoperative histological examination. In the present study, the status of the surgical margins and postoperative course were evaluated to determine any correlation between remnant carcinoma and postoperative survival. All consecutive patients who underwent resection for biliary tract cancer between January 2004 and May 2012 were identified from a database. Positive margin cases were divided into two groups, invasive carcinoma and carcinoma in situ (CIS). Immunohistochemical staining targeting Ki67 and p53 for positive margins was performed. Cases of major vessel invasion were significantly increased in the positive group compared with the negative group. The recurrence rate was significantly lower in the CIS group compared with the invasive group. The survival rate was significantly increased in the CIS group compared with the invasive group. The expression levels of p53 and Ki67 were significantly increased in the invasive group compared with the CIS group. No statistical correlations were observed between the expression of p53 or Ki67 and the survival or recurrence of disease. In the positive group, resected margin status was the principal factor associated with recurrence-free survival according to Cox-regression analysis. In conclusion, the status of the resected margins in the positive group was the most important factor for postoperative survival and recurrence in cholangiocarcinoma, not immunohistochemical staining targeting Ki67 and p53.